Dielectric functions, their properties and their relation to observables: Investigations using the Chapidif program for the case of aluminum - Vos, Maarten; Grande, Pedro L. (Computer physics communications, 2025)
We introduce the program ‘Chapidif’ by describing a study of the properties of aluminum based on simple model dielectric functions. These are generally not available from first principle, and one is forced to describe them in terms of (a sum of) model dielectric functions. The Chapidif program is used to visualize these, check their sum rules and the mathematical relation between the real and imaginary part. In addition, several properties related to the interaction of charged particles (here either protons or electrons) with matter are derived and compared with experiment. By having a single program that can calculate a range of properties, it becomes easy to ensure that the model used is not just able to describe a single observable, but it is transferable, i.e. describes reasonably well a larger range of material properties. A reflection electron energy loss measurement is used as an example of how a comparison of calculated results with experiment can be used to improve the model and thus enhance the quality of the properties derived from the dielectric function. Program Title: Chapidif CPC Library link to program files:https://doi.org/10.17632/7wmxg69v7x.1 Licensing provisions: CC BY NC 3.0 Programming language: Python, C++ Nature of problem: Frequency- and momentum-dependent dielectric functions can describe a wide variety of material properties. The quantity has many intricate mathematical properties and is subject to constraints due to sum rules. The Chapidif program can be used to visualize a dielectric function, check its sum rules, and calculate a wide range of quantities, in particular relating to the interaction of protons and electrons with matter. Details of how the classical and quantum-based dielectric functions are implemented are given elsewhere [1]. The program makes it easy to investigate if the assumed dielectric function has the required mathematical properties and how the choice of the model dielectric function and the corresponding parameters influences the calculated observables such as ion stopping and electron inelastic mean free path. Solution method: The program consists of a Python/Tkinter user interface and C++ backend that does the actual calculations. Results are displayed using Matplotlib library and, if desired, text-based output files containing the input parameters used and the calculated quantities can be generated. [1]M. Vos, P.L. Grande, RPA dielectric functions: streamlined approach to relaxation effects, binding and high momentum dispersion, J. Phys. Chem. Solids 198 (2025) 112470, https://doi.org/10.1016/j.jpcs.2024.112470. •The Chapidif program is introduced that can calculate and visualize dielectric functions and check their compliance with sum rules.•Chapidif enables consistent computation of multiple material properties from model dielectric functions within a single framework.•The program facilitates iterative refinement of dielectric models through direct comparison with experimental data, enhancing predictive accuracy.•It is demonstrated for the case of aluminum that, using a simple model dielectric function, the program can calculate a large range of materials properties.